Pengaruh Penggunaan Media Cotton Bud Painting Dalam Mengembangkan Kreativitas Anak Usia 5-6 Tahun Di PAUD Bina Iman Kota Bengkulu - Sumiati, Yulia; Nirwana, Evi Selva (Peneliti.net, 2024)
The aim of this research is to prove the effect of using cotton bud painting media in developing creativity and making painting and coloring activities a way to increase the creativity of group B1 children at Bina Iman PAUD Bengkulu City. This research uses a quasi-experimental method with a pretest-posttest control group design. The sample collection used a total sampling technique, because the population was less than 100. The sample in this study consisted of 20 children consisting of class B1 as an experimental class with 10 children and class B2 as a control class with 10 children. Data collection techniques use observation and documentation methods. Based on the analysis of the data obtained, it can be seen that there is a change in student learning outcomes, namely between pretest and posttest, in the experimental group it is 33.750 with a standard deviation of 9.284 and t-obtained 16.257. At a significance level of 0.05, the degree of freedom is 9. It can be seen that based on the results of the SPSS value assessment calculations, it is obtained that the significance value is 0.000<a value, namely 0.05. So Ho is rejected and Ha is accepted, meaning that there is an influence of cotton bud media on the development of children's creativity in Bina Iman PAUD Bengkulu City. ta Bengkulu.